Extended spectrum beta lactamase (ESBL)-producing Klebsiella pneumoniae clinical isolates and its susceptibility pattern to antibiotics at Dr. Soeradji Tirtonegoro General Hospital Klaten, Central Java - Kian Sinanjung; Hera Nirwati; Abu Tholib Aman (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Globally, the prevalence of Klebsiella pneumoniae (K. pneumonia) producing extended spectrum beta lactamase (ESBL) has been increasing steadily. The susceptibility patterns of ESBL-producing K. pneumonia varies considerably among countries. Therefore, the investigation of ESBL-producing K. pneumoniae in clinical isolates and their susceptibility are warranted. This research aimed to determine the proportion of ESBL-producing K. pneumoniae and the antibiotic susceptibility patterns of clinical isolates from Dr. Soeradji Tirtonegoro General Hospital, Klaten, Central Java. Identification of K. pneumoniae was performed by analyzing colony morphology, microscopic examination, and biochemical testing using Microbact. Both antibiotic susceptibility testing and ESBL screening (using ceftazidime, cefotaxime, and ceftriaxone discs) were conducted using disc diffusion method according to CLSI. The positive results were confirmed with modified double disk synergy (MDDST) using amoxicillin-clavulanate, ceftazidime, cefotaxime, and cefepime discs. From 962 clinical bacterial isolates, 168 (17.46%) isolates were identified as K. pneumoniae, during June 2017-May 2018. K. pneumoniae was mainly isolated from the Intensive Care Units (ICU) (29.17%) and with sputum being the most common specimen (45.24%). Overall ESBL producers were 52.98%, with the majority from ICU (41.57%) and isolated from sputum specimens (40.45%). ESBL-producing K. pneumoniae showed high resistance to many antibiotics. The sensitivity of ESBL-producing K. pneumoniae isolated from respiratory tract samples against piperacillin-tazobactam, amikacin, and meropenem was more than 80%. In conclusion, among all K. pneumoniae isolates, ESBL K. pneumoniae was 52.98%. ESBL K. pneumoniae from respiratory tract specimens had a sensitivity of more than 80% against piperacillin-tazobactam, amikacin, and meropenem.